Development of HOTS Problem-Based Test Instruments to Measure Level 4 Numeracy Capabilities Using Rasch Model - Saputri, Veni; Diana, Hafsah Adha (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Numeracy ability is one of the abilities measured in the Minimum Capability Assessment (AKM). Numeracy ability is very important to be improved because numeracy is not only doing mathematical calculations, but also a basis of knowledge and increases confidence to apply it practically. This research uses qualitative and quantitative approaches. This research method is research and development (R&D). The product developed in the form of a level 4 numeracy test instrument based on HOTS. The problem developed in the form of multiple choice questions and complex multiple choices is a number of 40 questions. The variables used as reference are validity, difficulty level, and reliability. This analysis was done with the help of Winsteps software. Based on winsteps program output obtained results according to rasch model with average values outfit MNSQ for persons and items respectively 0.89 and 0.91. The ZSTD Outfit values for persons and items are 0 and -0.01, respectively. While the reliability of the instrument expressed in alpha cronbach is worth 0.87.